2009
DOI: 10.1292/jvms.71.79
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Chondritis Associated with Systemic Joint and Cartilage Inflammation in a Cat

Abstract: ABSTRACT. An adult, Japanese domestic cat presented with bilateral swelling, distortion, and erythema of ears and deformation of the limbs. Biopsy of the pinnae confirmed auricular chondritis. These lesions and the cat's general condition subsequently deteriorated, and the cat died. At necropsy, chondral changes were present in the pinnae, costae, larynx, trachea, and limbs. Histopathologically, these chondral tissues showed marked deformation with lymphocytic inflammation. The limb joint inflammation was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
3
10
2
1
Order By: Relevance
“…Histologically, auricular cartilage necrosis/degeneration and fibroplasia, surrounded by inflammatory infiltrate, are the hallmarks of the disease in feline species (Delmage and Kelly, 2001;Gerber et al, 2002;Baba et al, 2009). The regenerative nodules of cartilage observed here were previously reported in a heifer, in mice with experimentally induced AC (Kitagaki et al, 2003;Kitagaki and Hirota, 2007;Adissu et al, 2014), and in a cat with RP (Baba et al, 2009).…”
Section: Tablesupporting
confidence: 76%
See 3 more Smart Citations
“…Histologically, auricular cartilage necrosis/degeneration and fibroplasia, surrounded by inflammatory infiltrate, are the hallmarks of the disease in feline species (Delmage and Kelly, 2001;Gerber et al, 2002;Baba et al, 2009). The regenerative nodules of cartilage observed here were previously reported in a heifer, in mice with experimentally induced AC (Kitagaki et al, 2003;Kitagaki and Hirota, 2007;Adissu et al, 2014), and in a cat with RP (Baba et al, 2009).…”
Section: Tablesupporting
confidence: 76%
“…Antigen, origin of the primary antibodies and dilutions used in the immunostaining protocols applied to the samples tissues of the cat Detection method: biotin-peroxidase-streptavidin; § Chromogen: DAB = 3,3′diaminobenzidine Immune-mediated inflammatory diseases are among the most challenging in terms of determining their pathogenesis and related injuries, as in the case of auricular chondritis (AC) in cats. Feline AC affects both ears with noninvolvement of other cartilaginous tissues and occurs predominantly in young and middle-aged short-haired cats (Delmage and Kelly, 2001;Gerber et al, 2002;Baba et al, 2009), as observed in the case reported here. Cats may also present involvement of the joints, respiratory, cardiovascular, ocular and other systems, in addition to the cartilage of the pinnae (Gerber et al, 2002;Baba et al, 2009), being similar to the relapsing polychondritis (RP) that affects middleaged humans (Lahmer et al, 2010;Arnaud et al, 2014;Cantarini et al, 2014).…”
Section: Tablesupporting
confidence: 71%
See 2 more Smart Citations
“…B. Abszesse durch Kampf-oder Bissverletzungen, bei der Katze auch aurikuläre Chondritis (▶ Abb. 2), [1,6,10]. • endokrine Erkrankungen (Hypothyreose, Hyperadrenokortizismus)…”
Section: Diagnostikunclassified